Encyclopedia of Medieval Royal Iconography - Vagnoni, Mirko (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Encyclopedia of Medieval Royal Iconography" sets out to be the first extensive collection of data on royal iconography from the Middles Ages (476-1492). In particular, it aims to collect entries about the most important rulers or dynasties that reigned during this period, from the Iberian Peninsula to Levant and from the Scandinavian Peninsula to the Mediterranean Sea. Specifically, "Encyclopedia of Medieval Royal Iconography" focuses on royal official images (namely, those representations that were commissioned at the behest of the ruler) and analyses them not only from an iconographic (namely, 'static') point of view but also as parts of a more general political communicative strategy (namely, in a 'dynamic' way) in order to better clarify their social functions and, consequently, their iconographic meanings. Thanks to this approach, "Encyclopedia of Medieval Royal Iconography" aims to offer a substantial overview on matters of medieval regal iconography and to be a useful tool for scholars who use royal images for their research.